2017
DOI: 10.1371/journal.pone.0182705
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomopathy-like properties of murine and human cancers

Abstract: Ribosomopathies comprise a heterogeneous group of hematologic and developmental disorders, often characterized by bone marrow failure, skeletal and other developmental abnormalities and cancer predisposition. They are associated with mutations and/or haplo-insufficiencies of ribosomal proteins (RPs) and inefficient ribosomal RNA (rRNA) processing. The resulting ribosomal stress induces the canonical p19ARF/Mdm2/p53 tumor suppressor pathway leading to proliferative arrest and/or apoptosis. It has been proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 52 publications
6
59
0
Order By: Relevance
“…Together, these data argue for a role for Rps26-deficient cells in cancer progression. Furthermore, these data also demonstrate that cancer cells have found diverse means to effect loss of ribosomal protein stoichiometry, including changes in RP gene expression (Ajore et al, 2017;Guimaraes and Zavolan, 2016;Kulkarni et al, 2017;Vlachos, 2017), downregulation of the assembly factor Ltv1 leading to substoichiometric, Rps3, Rps10 and Asc1/RACK1 (Collins et al, 2018), and bypass of Rio1, leading to Rps26-deficient ribosomes.…”
Section: Bypassing the Rio1 Checkpoint Disturbs Protein Homeostasis Amentioning
confidence: 65%
See 1 more Smart Citation
“…Together, these data argue for a role for Rps26-deficient cells in cancer progression. Furthermore, these data also demonstrate that cancer cells have found diverse means to effect loss of ribosomal protein stoichiometry, including changes in RP gene expression (Ajore et al, 2017;Guimaraes and Zavolan, 2016;Kulkarni et al, 2017;Vlachos, 2017), downregulation of the assembly factor Ltv1 leading to substoichiometric, Rps3, Rps10 and Asc1/RACK1 (Collins et al, 2018), and bypass of Rio1, leading to Rps26-deficient ribosomes.…”
Section: Bypassing the Rio1 Checkpoint Disturbs Protein Homeostasis Amentioning
confidence: 65%
“…haploinsufficiency results in a predisposition to the development of specific forms of cancer (Armistead and Triggs-Raine, 2014;Sulima et al, 2017;Vlachos, 2017), and furthermore, ribosomes from cancer cells often lose the stoichiometry of ribosomal proteins, including Rps26, which is correlated with poor patient outcomes (Ajore et al, 2017;Guimaraes and Zavolan, 2016;Kulkarni et al, 2017;Vlachos, 2017). Together, these data argue for a role for Rps26-deficient cells in cancer progression.…”
Section: Bypassing the Rio1 Checkpoint Disturbs Protein Homeostasis Amentioning
confidence: 99%
“…An alternative use of oxaloacetate, namely in gluconeogenesis, seems unlikely given the high rates of cell growth, the high glucose content of the cell culture medium used in these studies, and the fact that fibroblast gluconeogenesis is typically low (69,70). In addition to feedback inhibition of lactate dehydrogenase (LDH) by pyruvate and lactate (81), pyruvate carboxylase's 10 -30-fold lower K m value for pyruvate may also play a role (82)(83)(84)(85).…”
Section: Metabolic and Oncogenic Adaptations To Pdh Inactivationmentioning
confidence: 99%
“…Total lysates from WT and KO Rat1a-MycER cells were prepared in the presence of protease and phosphatase inhibitors as described previously (50,59,83). After SDS-PAGE, proteins were transformed to polyvinylidene difluoride membranes (Merck Millipore, Burlington, MA) and then probed with the antibodies listed in Table S2.…”
Section: Western Blottingmentioning
confidence: 99%
“…In murine models of hepatoblastoma and hepatocellular carcinoma (HCC), we have previously observed that most transcripts encoding the 80 proteins comprising the 40S and 60S ribosomal subunits were significantly increased relative to those in normal livers [9,10]. Because these increases were not uniform, the overall transcript expression patterns were altered as well.…”
Section: Introductionmentioning
confidence: 99%